2021
DOI: 10.3389/fmicb.2020.596541
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the First Virulent Phage Infecting Oenococcus oeni, the Queen of the Cellars

Abstract: There has been little exploration of how phages contribute to the diversity of the bacterial community associated with winemaking and may impact fermentations and product quality. Prophages of Oenococcus oeni, the most common species of lactic acid bacteria (LAB) associated with malolactic fermentation of wine, have been described, but no data is available regarding phages of O. oeni with true virulent lifestyles. The current study reports on the incidence and characterization of the first group of virulent oe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…In previous studies, we have shown that the OE33PA adhesion device has three components: Dit, Tal, and RBP. Meanwhile, only two components, Dit and Tal, make up that of Vinitor162 [ 4 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, we have shown that the OE33PA adhesion device has three components: Dit, Tal, and RBP. Meanwhile, only two components, Dit and Tal, make up that of Vinitor162 [ 4 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Vinitor162 has only two putative proteins building its adhesion device: a Dit and a long and extended Tal [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations